2014
DOI: 10.1186/s13048-014-0087-1
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of SOX7 in ovarian cancer: a novel tumor suppressor through the Wnt/β-catenin signaling pathway

Abstract: BackgroundProducts of the SOX gene family play important roles in the life process. One of the members, SOX7, is associated with the development of a variety of cancers as a tumor suppression factor, but its relevance with ovarian cancer was unclear. In this study, we investigated the involvement of SOX7 in the progression and prognosis of epithelial ovarian cancer (EOC) and the involved mechanisms.MethodsExpression profiles in two independent microarray data sets were analyzed for SOX7 between malignant and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 27 publications
3
33
0
Order By: Relevance
“…It is hardly detectable at the early stage, largely due to the lack of specific symptoms and reliable screening [2], so, surgical resection and subsequent chemotherapy are still the major therapeutic strategies [3]. However, the efficacy of chemotherapy is limited by chemoresistance [4].…”
Section: Introductionmentioning
confidence: 99%
“…It is hardly detectable at the early stage, largely due to the lack of specific symptoms and reliable screening [2], so, surgical resection and subsequent chemotherapy are still the major therapeutic strategies [3]. However, the efficacy of chemotherapy is limited by chemoresistance [4].…”
Section: Introductionmentioning
confidence: 99%
“…Low level of SOX7 together with increased cyclooxygenase-2 and cyclin-D1 were detected in tissues from patients with epithelial OC, especially in patients with advanced serous cystadenocarcinoma 10 . This suggested that SOX7 might regulate cell proliferation by influencing the Wnt/β-catenin signaling pathway.…”
Section: Sox Genes In Gcsmentioning
confidence: 97%
“…Thus, there is an urgent need to find novel diagnostic biomarkers for detecting OC at a premalignant stage 33 . SOX genes are identified as such biomarkers that can contribute to early screening and the prediction of clinical features in patients with OC, and regulation of SOX gene expression could influence cell proliferation and treatment efficacy at the cellular level 9,10,16,18,31,34 . …”
Section: Sox Genes In Gcsmentioning
confidence: 99%
See 2 more Smart Citations